Netnography : Gojek Marketing Strategy Analysis Through YouTube Social Media. - Siti Fatimah; Mirza Chusnainy; Fifi Khumairo; Shinta Didin Hari Mariana; Sigit Hermawan (Media Ekonomi dan Manajemen, 2021)
PT Aplikasi Karya Anak Bangsa or Gojek is an online transportation service company that was founded in 2010.The research objective is to analyze and describe Gojek's marketing strategy through YouTube social media. This research uses a qualitative approach, with analysis using netnographic studies. The research subjects are 20 netizens who commented on Gojek's Indonesian Youtube account related to the video marketing advertising Gojek. The results showed that Gojek's marketing strategy made use of the internet as a means to promote the services offered. The promotion process is very intensively carried out by the Gojek Company, one of which is through social media. With the sophistication of advertising done through media social, users will automatically be treated to various promotions from the CompanyGojek when opening its social media pages. This strategy is very appropriate because almost the entire process of purchasing a Gojek service is done ina smartphone application, this means that the potential consumers targeted are in accordance with the ad audience that is installed. The conclusion in this study is the implementation of marketing 7P on online Gojek services which include: product, price, place, people, process, and physical evidence has been implemented well.